Investigating Difficulties and Decisions in Information Visualization Design - Ferreira, Bruna Moraes; Rodrigues, Ariane Moraes Bueno; Barbosa, Gabriel Diniz Junqueira; Barbosa, Simone Diniz Junqueira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Interpreting and creating data visualizations is an essential skill in the data-intensive age. Visualizations are a tool to extract and communicate information from data. However, people often need help in creating visualizations. Understanding the existing difficulties and investigating ways to improve data visualization design aims to empower novices’ data exploration. This research focuses on investigating the visualization design process to identify aspects to support novices in information visualization design and education. We performed an in-depth empirical study with five practitioners in the software industry but novices in data visualization. The participants selected visualizations to answer six analytical questions. The creation process was conducted by a researcher and recorded by video. In total, the participants created 63 visualizations. We analyzed the videos and extracted the steps followed in this process. Also, two visualization experts inspected the content participants had created and identified problems in selecting the visualization type and designing the visualization. As a result, we identified difficulties in selecting appropriate visualizations, mapping data into visual variables correctly, and some issues used as the basis for decisions during the design process.